Analisis Kualitas Audit Aparat Pengawasan Internal Pemerintah Ditinjau Dari Kompetensi, Independensi, Dan Motivasi - Eri Kurniawan (Universitas Islam Kadiri, 2020)
regional inspectorate officersand to determine the effect of competence, independence, and motivation to audit quality officials in Inspectorate Region of Blitar City. Competence, independence, and motivation of auditors to play a role in determining the quality of the audit will also affect the quality of the work of auditors. The purpose of this study was. This study uses primary data. The population in this study were all Blitar City Inspectorate officers who participated in the inspection tasks totaling 35 people, all members elected as members of the sample population (census). The data taken from questionaires distributed to respondents. The independent variable (independent) is competence, independence and motivation, while the bound variable (dependent) is the quality of audits. Data were analyzed using multiple linear regression analysis (multiple regretion). The results showed that the competence and motivation have a positive and significant impact on audit quality, while the independence of the variables do not have a significant impact on audit quality. Implications of these findings for efforts to realization of a quality audit is the need for providing motivation to the auditor about the urgency of a quality audit in addition to efforts to increase the competence through training.